Telaah Tipologis terhadap Antusiasme Siswa dalam Menggunakan Teknologi Informasi dan Komunikasi pada Mata Pelajaran PAI - Niam, Khoirul; Wahyuningsih, Retno (An-Nuha, 2025)
The integration of Information and Communication Technology (ICT) into Islamic Religious Education (PAI) is expected to improve student engagement and learning outcomes. However, variations in student responses indicate differing levels of digital readiness. This study aims to explore the typology of student enthusiasm in using ICT in PAI at SD Negeri 1 Gondang. Using a qualitative case study approach, data were collected through participatory observation, interviews, and documentation, and analyzed using Spradley’s model. The findings show three typologies of enthusiasm: high (73.7%), moderate (18.4%), and low (7.9%), influenced by access to digital devices, previous experience, and teacher support. Students with regular digital access and supportive environments demonstrated higher enthusiasm. The study concludes that ICT-based learning in PAI should consider students' digital readiness. These results support Keller’s ARCS motivation model and highlight the importance of addressing the digital divide in primary religious education